Increasing Knowledge and Effectiveness of Saiyo Farmers in The Koto Nan IV Ranah Pesisir - Jeni Dwi Marta (Universitas Negeri Padang, 2020)
This research is based on the knowledge and effectiveness of the Pasa Saiyo Farmers Group in the Koto Nan IV area of Coastal Areas. Research objectives (1) describe the level of success (2) describe the level of farm income (3) describe the satisfaction of the results obtained. Type of quantitative descriptive research, a population of 30 people, research data collection techniques in the form of a questionnaire (questionnaire) while the data analysis technique uses percentages.Keywords: Upgrade, Knowledge, Effectiveness, Farmer Groups